Bie-Jia-Ruan-Mai-Tang, a Chinese Medicine Formula, Inhibits Retinal Neovascularization in Diabetic Mice Through Inducing the Apoptosis of Retinal Vascular Endothelial Cells - Liu, Qiu-Ping; Chen, Yu-Ying; Yu, Yuan-Yuan; An, Pei; Xing, Yi-Zhuo; Yang, Hong-Xuan; Zhang, Yin-Jian; Rahman, Khalid; Zhang, Lei; Luan, Xin; Zhang, Hong (Frontiers in Cardiovascular Medicine, 2022)
Proliferative diabetic retinopathy (PDR) is one of the main complications of diabetes mainly caused by the aberrant proliferation of retinal vascular endothelial cells and formation of new blood vessels. Traditional Chinese medicine possesses great potential in the prevention and treatment of PDR. Bie-Jia-Ruan-Mai-Tang (BJ), a Chinese medicine formula, has good therapeutic effect on PDR clinically, however, the mechanism of action involved remains unclear. Therefore, we investigated the effect of BJ on PDR through in vitro and in vivo experiments. A diabetic mouse model with PDR was established by feeding high-fat-high-glucose diet combined with intraperitoneal injection of STZ while high glucose-exposed HRCECs were employed to mimic PDR in vitro. The in vivo experiments indicated that BJ inhibited the formation of acellular capillaries, decreased the expression of VEGF and increased the level of ZO-1 in diabetic mice retina. In vitro experiments showed that high glucose significantly promoted cell viability and proliferation. However, BJ induced cell proliferation inhibition, cycle arrest in S phase, apoptosis and ROS increase, decreased mitochondrial membrane potential, reduced ATP production and the expression of p-PI3K, p-AKT and Bcl-xL, but increased the expression of Bax and p-NF-κB. These results suggest that BJ induces the apoptosis of HRCECs exposed to high glucose through activating the mitochondrial death pathway by decrease of PI3K/AKT signaling and increase of NF-κB signaling to inhibit the formation of acellular capillaries in retina, thus impeding the development of PDR.